Short-term Recovery After Displaced Adolescent Clavicle Fractures: Do Differences an Exist Between Surgical and Non-Surgical Treatments?...Pediatric Research in Sports Medicine (PRiSM) 9th Annual Meeting, January 27-29, 2022, Houston, Texas. - Block, Andrew M.; Ganapathy, Aravinda; Nepple, Jeffrey J. (Orthopaedic Journal of Sports Medicine)
Introduction: Clavicle fractures are common in the young, active adolescent population. It is increasingly recognized that displaced clavicle fractures treated either conservatively or surgically have good outcomes at 1 year. Currently, it is not well established whether any differences in the short-term recovery (<3 months) exist. Patient-Reported Outcomes Measurements Information System (PROMIS) computer adaptive testing (CAT) has been shown to be a valid and reliable means to assess PROs. Purpose: To compare short-term recovery between surgical and non-surgical treatment of displaced clavicle fractures in adolescents utilizing PROMIS. Methods: Patients with displaced clavicle fractures were assessed prospectively utilizing PROMIS at each clinic visit. Patients completed the Pediatric PROMIS CAT domains Upper Extremity Function and Pain Interference. Inclusion criteria included patients <18 years old, treatment either surgically or conservatively, and at least two follow up time points within 2 months post-op. Time points were calculated as <10 days, 7-21 days, 6 weeks (22-52 days), and 3 month (70-110 days) post-injury. Time points were compared utilizing a mixed-linear regression model. Ceiling or Floor Effects were present when ≥15% of study cohort had reached the maximum or minimum possible score. Results: A total of 52 patients with displaced clavicle fractures were identified (26 surgically treated and 26 conservatively treated). Mean age was similar (15.4 v. 14.1, respectively). No differences in mean PROMIS scores between treatment modalities were present at baseline (p>0.05). For Pain Interference and Upper Extremity Function, significant improvement by 6 weeks was seen in both surgically and conservatively treated patients (Figure 1). For Pain Interference, significant improvement by 6 weeks was seen in both surgically (Δ=-6.8, p=0.03) and conservatively treated patients (Δ=-8.3, p=0.003). More surgically treated patients reached a floor effect for Pain Interference at 6 weeks (24%), compared to conservatively treated patients (4%). For the Upper Extremity function, significant improvement was seen by 6 weeks in both surgically (Δ=7.2, p=0.042) and conservatively (Δ=11.9, p=0.003) treated patients. For UE Function, 21% of surgically treated patients reached a ceiling effect at 6 weeks, compared to 13% for conservative treatment (p>0.05). No differences were present at 3 months post-injury. Conclusions: While both surgical and conservative treatment of adolescent displaced clavicle fractures demonstrate similar trends of PROMIS recovery, surgical treatment may allow for rapid recovery at 6 weeks compared to conservative treatment in some patients.